POOR READING HABIT: AT GLANCE REFLECTION - Erna Iftanti (Pusat Pengembangan Bahasa IAIN Tulungagung, 2010)
English plays a very great role with the progress of globalization as a common international language for living in the 21st century. Thus, it is significant to promote the Indonesian students to acquire good literacy in both reading and writing in English. To achieve this, English which is comprised of language skills and components, in Indonesia, is learnt formally from elementary school to tertiary level of education. However, reading is as the basic underlying skill that people should have and the development of reading skills serves as the major foundational academic ability for all school-based learning. Yet, the length of study time and the important of English and English instruction does not promote the students’ good reading habit yet. Reading has still been as the most difficult activity. Therefore, the teaching and learning of English, particularly on the teaching of reading need to be reconsidered. All elements of society, such as government, teachers, students, and parents are responsible for the improvement of this English language teaching and learning particularly to promote good reading habit.